Testing of antimicrobial activity of preservatives for dental gels development - Maslii, Yu; Ruban, O; Kaliuzhnaia, O; Khokhlenkova, N (Annals of Mechnikov's Institute, 2020)
Introduction. Given the widespread prevalence of oral diseases, especially pathologies of periodontal tissues and mucous membranes, among the population of different ages and the needs of the pharmaceutical market in topical drugs for their treatment, the development of new domestic dental drugs is relevant. The most common topical dosage form in dental practice is gels, which are characterized by good distribution on the tissues of the oral cavity, prolonging effect and high bioavailability. At the Industrial Technology of Drugs Department of National University of Pharmacy, two dental gels are being developed under the name "Cholident" and "Lysostom". Previous studies showed that freshly prepared gels satisfied the requirements of SPhU for microbiological purity. However, contamination of the samples by test-microorganisms caused their intensive growth, which proved necessity for introduction of antimicrobial preservatives into the gels. These adjuvants prolong the shelf life of pharmaceutical products, increase their resistance to spoilage after opening the package, especially in the case of using multi-dose containers, and, accordingly, prevent infection of the patient. The aim of this work was selection of effective antimicrobial preservatives in rational concentrations for the composition of dental gels "Cholident" and "Lysostom". Materials & methods. The following ingredients were selected as preservatives in the gels are being developed: benzoic acid, sodium benzoate, sorbic acid, potassium sorbate, methyl parahydroxybenzoate (nipagin), propyl parahydroxybenzoate (nipazol). The concentration of preservatives for all gel samples was 0.1 % and 0.2 %. They have much lower toxicity than others, are harmless to humans even in large quantities and are permitted for the preservation of food and pharmaceutical products. The selection of preservative for the composition of dental gels "Cholident" and "Lysostom" was based on the study of its antimicrobial activity. Preservatives effectiveness tests were carried out according to the method of SPhU 2.3, Ch. 5.1.3. According to the requirements of SPhU, the sterility test of culture medium and solvent: growth properties of culture medium (soy-casein culture medium – for bacterial cells growth and Saburo-dextrose medium without antibiotics – for fungal cells) and suitability test of methods for determining the total number of cells were performed. Results & discussion. Tests have shown that for dental gel "Lysostom" with preservatives nipagin, sodium benzoate, potassium sorbate, it could be noted that the obtained data satisfy the requirements of SPhU for oral drugs. Among the preservatives listed above, sodium benzoate at a concentration of 0.2 % had the highest antimicrobial activity. The results of antimicrobial preservatives efficacy determination in the composition of the dental gel "Cholident" proved SPhU eligibility for all samples. The combination of nipagin : nipazol had the highest antimicrobial activity against all test-microorganisms, and, taking into account the requirements of economy and safety, their use at a concentration of 0.1 % will be sufficient. Conclusion. Thus, tests of the antimicrobial preservatives effectiveness in the experimental samples of dental gels "Lysostom" and "Cholident" proved that all the studied preservatives, namely sodium benzoate, potassium sorbate, nipagin and combination nipagin with nipazol, benzoic acid and sorbic acid, had high antimicrobial efficacy and met the requirements of SPhU for oral drugs. Taking into account a slightly higher antimicrobial activity, the sodium benzoate at a concentration 0.2 % was selected as the most acceptable preservative for the gel "Lysostom". The combination nipagin : nipazol (3:1) was chosen as the most promising preservative for the gel "Cholident", which provided at a concentration 0.1 % stronger than other preservatives antimicrobial action. DOI: 10.5281/zenodo.3885062